Gender violence and risk of feminicide in pupils from public and private universities in Lima Metropolitana - Velásquez Centeno, Carlos (2020)
The objective of the study is to evaluate the relationship between attitudes towards gender violence and the risk of extreme violence towards the couple or feminicide in female students of public and private universities of Metropolitan Lima, being the instruments to use the Attitude Scale Towards Violence Gender and Risk Assessment Scale. The instruments are applied on a sample of students from public and private universities in the areas of Health Sciences. The general results indicate that the greater the attitude of rejection of violence, there is less experimentation of violence; women from private universities experience greater physical, sexual and economic violence, and less rejection of gender violence; young people show a greater rejection of violence than adults; women who have a partner experience greater psychological and economic violence; and self-employed people are those who consider suffering the greatest violence in all types compared to those employed and unemployed.